Prevailing Socio-Cultural Factors and their Impact on the Business Environment - Dr. Maneesha Kaushik, Priyanka Payal (International Journal of Advanced Science and Technology, 2020)
The business environment or environment of a nation cannot exist without being affected by the prevailing conditions or environment.  Under the commercial environment, a person has included all the actions performed by a person for his idol or for the purpose of earning money.  These actions performed by human beings to earn their living are called economic activities.  These economic activities are influenced by the geographical, religious, social, cultural, political, etc. environment around man.  When a man completes these economic activities, at that time, he does not forget his society, society and religion-related things and rules.  Therefore, his economic activities cannot exist without being influenced by the environment around him.  While the economic activities of another man are affected by his environment, on the other hand, their economic activities also affect the environment.  This is the reason why today man is trying to harmonize with the environment or environment for the success of his economic activities. The paper focus on components of the social environment, social objectives of business which protect consumer interest, protect the interests of workers and protect the interests of the society. Social environment of India and under development is also part of the study. To study also focuses on how culture has a unique role in the business environment.